SPIRITUA L AND MORAL EDUCATION OF ADOLESCENTS AS A TOOL FOR CONFLICT PREVENTION IN THE SOCIO-POLITICAL LIFE OF SOCIETY - Abitkhan Sabitkhanovich Shakirov (Web of Journals Publishing, 2024)
The subject of the article. This article analyzes the spiritual and moral education of adolescents and high school students as a prevention not only of interpersonal conflicts, but also of interracial, interethnic, and interreligious conflicts. The moral education of high school teenagers in the modern multicultural environment of a comprehensive school is also considered. Pedagogical problems for the implementation of moral education are revealed, including the variability of methodological approaches, how complex the psychological mechanisms of moral education are, age-related features of the formation of moral qualities of a teenager's personality. The concept of a multicultural educational environment is revealed and the ways of its pedagogical potential in the moral education of a teenager are shown.
Keywords: Moral education, adolescents, interpersonal conflict, prevention, interreligious conflicts, social conflicts, multicultural environment, pedagogical problems, national traditions, religious institutions.